A Review of Endothelium-Dependent And-Independent Vasodilation Induced by Phytochemicals in Isolated Rat Aorta - Martinez-Salinas, J; Morales-Munoz, B (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
This review discusses the contribution of the use of the isolated rat aorta (IRA) as a model for the evaluation of extracts and metabolites produced by plants with a vasodilator effect in animals. This model continues to be a valuable approach for the search and development of new phytochemicals consumed as medicinal plants or foods. In most cases, the sources of phytochemicals have been used in folk medicine to treat ailments that include hypertension. In this model, the endothelium is emphasized as a key component that modulates the vessel contractility, and therefore the basal tone and blood pressure. Based on the functional nature of the model, we focused on studies that determined the endothelium-dependent and-independent vasodilatory activity of phytochemicals. We describe the mechanisms that account for aorta contraction and relaxation, and subsequently show the vasoactive effect of a series of phytochemicals acting as vasodilators and its endothelium dependence. We highlight information regarding the cardiovascular benefits of phytochemicals, especially their potential antihypertensive effect. On this basis, we discuss the advantages of the IRA as a predictive model to support the research and development of new drugs that may be of help in the prevention and treatment of cardiovascular diseases, the number one cause of death worldwide. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.